PTU-049 Modulation of toll-like receptor genes with selective gut decontamination in cirrhotic animals prevents the development of acute-on chronic liver failure (ACLF). (28th May 2012) - Shah, N; Dhar, D; Davies, N A; Mookerjee, R P; Jalan, R
Abstract : Introduction: Acute deterioration in the liver function following precipitating illness in patients with cirrhosis often lead to multiple organ failure. Inflammation is thought to be a major contributing factor. We hypothesised that toll like receptor's (TLRs) play a pivotal role in lipopolysaccharide (LPS) mediated cytokine surge in patients with cirrhosis culminating in acute-on-chronic liver failure (ACLF). Selective gut decontamination with Norfloxacin would dampen this inflammatory cascade. Methods: Global hepatic gene expression was studied in a rodent model of cirrhosis induced by bile duct ligation (BDL) (Agilent microarray) and compared the results to sham animals. TLR related genes were among the differentially expressed genes in the liver. We validated gene expression in the Liver and Kidney in a second set of experiment in Sham, BDL, BDL+LPS, BDL+Norfloxacin, BDL+Norfloxacin+LPS groups using the quantitative real-time PCR. Cytokines (Becton Dickenson) and biochemistry were measured (COBAS Integra 400). Results: Among the several genes with high expression in the BDL group as detected by the microarray, both TLR 4 and 2 had significantly higher expression in liver and Kidney compared with the sham group. We also found a marked upregulation of the C-C motif ligand 2 (CCl2) and C-X-C motif ligand 2(CxCl2) Furthermore, LPS administration in BDL animals accentuated not only the TLRs (4 and 2) expression in both kidney and liver but also the Cxcl2 and CCl2 in both these organs associated with deterioration organ function as suggested with a rise in the liver enzyme, creatinine and a rise in plasma and tissue cytokines. Norfloxacin pre-treatment in BDL group (BDL+Norfloxacin) attenuated the TLR4 and TLR2 expression in both liver and kidney. Selective decontamination with Norfloxacin in BDL +LPS animals limited the upregulation of TLR4 and TLR2 in the Liver and Kidney. It also prevented the upregulation of the CxcL2 and CCl2 in both these organs. This was associated with significant improvement in liver enzymes, creatinine and cytokines. Conclusion: This study shows that the liver and kidneys in cirrhotic animals are primed by upregulation of TLR's and its downstream inflammatory mediators in the Liver and Kidney which make them exquisitely sensitive to the effects of superimposed infection/inflammation leading to organ failure. Selective decontamination with Norfloxacin prevents the progression of ACLF by reducing gene expression of TLR 2 and 4 and its associated inflammatory adaptors. Competing interests: None declared.